Human Hookworm Infection Enhances Mycobacterial Growth Inhibition and Associates With Reduced Risk of Tuberculosis Infection - O'Shea, Matthew K.; Fletcher, Thomas E.; Muller, Julius; Tanner, Rachel; Matsumiya, Magali; Bailey, J. Wendi; Jones, Jayne; Smith, Steven G.; Koh, Gavin; Horsnell, William G.; Beeching, Nicholas J.; Dunbar, James; et al. (Frontiers in Immunology, 2018)
Soil-transmitted helminths and Mycobacterium tuberculosis frequently coincide geographically and it is hypothesized that gastrointestinal helminth infection may exacerbate tuberculosis (TB) disease by suppression of Th1 and Th17 responses. However, few studies have focused on latent TB infection (LTBI), which predominates globally. We performed a large observational study of healthy adults migrating from Nepal to the UK (n = 645). Individuals were screened for LTBI and gastrointestinal parasite infections. A significant negative association between hookworm and LTBI-positivity was seen (OR = 0.221; p = 0.039). Hookworm infection treatment did not affect LTBI conversions. Blood from individuals with hookworm had a significantly greater ability to control virulent mycobacterial growth in vitro than from those without, which was lost following hookworm treatment. There was a significant negative relationship between mycobacterial growth and eosinophil counts. Eosinophil-associated differential gene expression characterized the whole blood transcriptome of hookworm infection and correlated with improved mycobacterial control. These data provide a potential alternative explanation for the reduced prevalence of LTBI among individuals with hookworm infection, and possibly an anti-mycobacterial role for helminth-induced eosinophils.